Scaffolding as a cognitive load reduction strategy for teaching atomic and nuclear physics - Appiah-Twumasi, Eric (Momentum: Physics Education Journal, 2024)
This study investigated the effectiveness of scaffolding as a cognitive load reduction strategy for teaching Atomic and Nuclear Physics. This study was carried out with the participation of university physics students (n = 20) enrolled in the B.Sc. Physics Education Programme.  A quasi-experimental one-group pre-test-post-test design was used to collect both quantitative and qualitative data on physics students’ conceptual understanding and learning dispositions about Atomic and Nuclear Physics. The intervention consisted of a university academic calendar of one semester (2022-2023) using scaffolding as a cognitive load reduction strategy. The baseline assessment revealed that the respondents had incorrect, partial, and no knowledge of electron transition and radioactivity-related concepts. However, the post-test analysis revealed a mean score of 7.22 (SD = 0.31) that can be considered significant (p < 0.05) and a large effect of 0.79 on the conceptual understanding of the participants in Atomic and Nuclear Physics. The study findings also revealed that the participants' factual, conceptual, procedural, and meta-cognition about Atomic and Nuclear Physics improved after using scaffolding as a cognitive load reduction strategy. The results further revealed an improved learning disposition about Atomic and Nuclear Physics among the participants after the intervention.  The participants articulated, among others, that the use of scaffolds as a cognitive load reduction strategy stimulated their interests, made the topic more enjoyable, and reduced their sense of hopelessness. The author accordingly recommends scaffolding as a cognitive load reduction strategy to physics educators for effective teaching and learning in the context of Atomic and Nuclear Physics.